Euterpe oleracea-based biochar for clonazepam adsorption: synthesis, characterization, adsorption properties, and toxicity assays (2023)
The consumption of açaí fruit (Euterpe oleracea) has largely increased worldwide, resulting in a significant increase in the demand for its pulp. As a result, the small producing communities end up with large amounts of açaí endocarp residues, creating local environmental pollution problems. Therefore, chemical and physical routes were investigated for producing açaí endocarp adsorbents to propose a locally viable solution for this problem. The adsorption properties of the produced biochars were tested for clonazepam (CZM) removal, and the toxicity of the final solutions was evaluated. The results revealed that the chemical route generated biochar with about twice the surface area and pore volume (762 m2 g−1 and 0.098 cm3 g−1) than the physical route (498 m2 g−1 and 0.048 cm3 g−1). Furthermore, the Sips isotherm better described the CZM adsorption equilibrium for both biochars, with qs values of 26.94 and 61.86 mg g−1 for the physical- and chemical-activated adsorbents. Moreover, recycling studies were performed, and the chemical-activated biochar was stable for up to three cycles, reaching removal rates superior to 80%. Besides, the final toxicity decreased after the adsorptive treatment. Therefore, chemical activation can be used as a simple and effective method for producing stable and compelling adsorbents as an elegant way of adding value to the residues from açaí production, helping solve local environmental problems.